Stress of the nurses who work on different hospital departments: a descriptive study - Pires da Rocha, Maria Cecília; De Martino, Milva Maria Figueiredo; Ferreira, Luciane Ruiz Carmona (Online Brazilian Journal of Nursing, 2009)
This study aimed to analyze the stress levels of nurses working in different sectors of the morning, afternoon and night; characterize the stressors of different sectors and compare the level of stress variables. This study was quantitative, descriptive, transversal and comparative study conducted in a hospital in the city of Campinas, São Paulo, Brazil. We used to collect data an identification form and scale of stress modified Bianchi (EBEM). The study population consisted of 203 subjects of the various shifts, and 59.6% of the day, 65% open areas, 88.2% female, mean age of 39.6 years. The stress score was 2.60 (average level of stress). Among the nurses were supervisors incidence of 79% with medium level of stress and 10.5% with early and high level of stress. Among the nurses, 48.3% had medium level of stress and 40.0% with early and high level of stress. We concluded that stress was present, regardless of sector of work, but the lack of human resources to cover the shift, the lack of material and / or equipment to assist and work with technically disqualified were the stressors with higher scores of stress.